Bio-sorption of copper and lead ions in single and binary systems onto banana peels. Issue 1 (1st January 2021) - Afolabi, Felicia O; Musonge, Paul; Bakare, Babatunde F
Abstract: It is very rare to have the ions of only one metal ion in wastewater. Hence, the removal of copper and lead ions from aqueous solution in single and binary systems using natural banana peels was investigated in a batch mode. Banana peels were characterised using FTIR, which gave the functional groups present. The spectra of banana peels loaded with Pb(II) had a higher percentage transmittance after adsorption. The point of zero charge pHpzc of banana peel was found to be 4.83 which makes it suitable for the adsorption of cations. Kinetic and isotherm studies were carried out at a pH of 5.5, concentration range of 10–100 mg/L, and adsorbent dosage range of 0.1–1 g. A pseudo-second order model is fitted to the kinetic data suggesting chemical adsorption. The Langmuir isotherm performed well with the experimental data which means adsorption occurred as a monolayer on the surface of banana peels. The maximum adsorption capacity of Pb(II) for Langmuir isotherm was 66.67 mg/g. This indicated that in the single system banana peels have more affinity for Pb(II) than for Cu(II). At higher concentrations, the experimental data for the isotherm study showed the effect of a competitive phenomenon which affected only Cu(II) in the binary system. Natural banana peels are efficient agricultural waste materials that can be used for the treatment of wastewater contaminated with copper and lead ions.